Proposal for a new method for analyzing the domino effect in an oil refinery and its impact on the environment - M SMAIAH; M DJBABRA; L BOUBAKER (Management of Environmental Quality, 2019)
Purpose The purpose of this paper is to propose a new managerial method to integrate the environmental dimension in the domino effects (DEs) analysis. Design/methodology/approach The proposed method is a three-step approach: identification of primary hazards in the form of potential events causing the DE, a mixed quantification (deterministic and probabilistic) of the risk of the DEs with a view to its control and capitalizing the results from the BLEVESOFT software as well as those relating to the probability of occurrence of the DEs in the form of a prioritized action plan dedicated to surrounding environments (proximity territory). Findings The primary hazards are technologically manageable at the studied system but are unpredictable if triggered at the environmental subsystem because they are difficult to be managed and often cause panic, which is a form of a very catastrophic DE. Research limitations/implications The research could affect members of the engineering and construction industry, and can be applied in several domains since it studies the DE phenomenon. which is a common problem especially in industrials plants. Practical implications The proposal method is applied in an industrial terminal in Algeria. Originality/value This paper presents an exploratory study of using a new managerial method that aims to combine the potentialities of geomatic sciences that allow the spatial representation of nearby territories to assess the severity of DEs through a deterministic approach, and the modeling of DEs as well as their analysis by a probabilistic approach.